2000
DOI: 10.1088/0022-3727/33/3/317
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and bonding of hydrogen near a fcc Fe stacking fault

Abstract: The atom superposition and electron delocalization molecular orbital (ASED-MO) semiempirical method is used to analyse the atomic hydrogen-Fe interaction. The face centred cubic (fcc) Fe model contains a stacking fault and as a comparison the H-fcc Fe (normal) system is also studied. The solid is represented by a cluster of 180 metallic atoms distributed in five layers. The interstitial atoms localized in different geometric positions found an energetic minimum in a zone close to octahedral interstitial holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, the atomistic simulation of the hydrogen effect on the dissociation of screw dislocations, as carried out using the embedded-atom method (EAM) for Ni-H interaction in Ni [22], demonstrated that the homogeneously distributed hydrogen atoms in the slip plane can increase the separation between partials and, thus, induce slip planarity. The results for bulk binding energies indicate that, if hydrogen atoms occupy octahedral sites, the total energy of the crystal lattice decreases [23]. In this situation the Fe-H electronic interaction is favourable and the stacking fault region could act as a trap.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the atomistic simulation of the hydrogen effect on the dissociation of screw dislocations, as carried out using the embedded-atom method (EAM) for Ni-H interaction in Ni [22], demonstrated that the homogeneously distributed hydrogen atoms in the slip plane can increase the separation between partials and, thus, induce slip planarity. The results for bulk binding energies indicate that, if hydrogen atoms occupy octahedral sites, the total energy of the crystal lattice decreases [23]. In this situation the Fe-H electronic interaction is favourable and the stacking fault region could act as a trap.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that H reduces the SFE of austenitic stainless steel and thereby increases the strain hardening either by retarding cross-slip or by promoting deformation twinning. 19) In the present work, the H-charged TWIP steel samples had a lower strain hardening than the H-free TWIP samples. The lower strain hardening of the Hcharged TWIP steel resulted in a lower uniform elongation (Fig.…”
Section: H-charging Of Twip Steelmentioning
confidence: 48%
“…This bond strength reduction is expected to make the structure more deformable. 19) A low SFE leads to less cross slip and a more planar glide, both of which are essential for obtaining an increase in strain hardening by reducing the dislocation recovery rate.…”
Section: Introductionmentioning
confidence: 99%
“…The SF acts as a trap for H [36] and could act as a trap for C. In previous works, our group has reported that the addition of a C atom in a Fe FCC matrix that contains a SF decreases the strength of the local Fe-Fe bond to about 78% of its original value. This bond weakening is a consequence of C-Fe bond that is formed at the expense of the Fe-Fe neighbors bonding [36][37][38].…”
mentioning
confidence: 99%